Treaties of Peace in the Conquests of Persia: A Historical Reading - Sadiq, Ass.Prof Fadel Kazem (Thi Qar Arts Journal, 2024)
The historical significance of the peace treaties concluded by the leaders of the Islamic armies with the chiefs and inhabitants of the cities of Persia lies in their high emphasis on how the Muslim armies dealt with the Persian inhabitants. The essence of these treaties was characterized by tolerance and leniency, which are core principles of the noble Islamic religion. These treaties are not only important historical documents but are also dated and witnessed by individuals. This research attempts to trace the historical and documentary importance of these treaties through three sections. The first section explains the meanings of covenant and peace in the Holy Quran and the Hadith of the Prophet. The second section discusses the rights and facilities granted by the Muslim conquerors to the inhabitants of these cities, including safety, protection of lives and property, and freedom to practice religious rituals. The third section addresses the duties and obligations of these inhabitants towards the Muslims, including paying the jizya (tax), providing assistance, and refraining from betrayal and treachery against the Muslims.